ChemInform Abstract: Microwave‐Assisted Synthesis of Coumarin‐3‐carboxylic Acids under Ytterbium Triflate Catalysis. Issue 34 (August 2015) - Fiorito, Serena; Genovese, Salvatore; Taddeo, Vito Alessandro; Epifano, Francesco
Abstract A simple solvent‐free protocol for the condensation reaction of 2‐hydroxybenzaldehydes or 2‐hydroxyacetophenones with Meldrum′s acid to afford the title products in good to excellent yields is developed.